A STUDY ON IMPORTANT INTERCONNECTION BUSINESS SUCCESSES WITH SUPPLY CHAIN AND LOGISTICS MANAGEMENT - Bangar, Amol Arjunrao; Kulkarni, Milind Audumbar; Phadke, Supriya Abhijit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The seamless connection, between logistics and supply chain management plays a role in the success of businesses operating in today’s changing global marketplace. The purpose of this study is to explore the synergies between these two areas focusing on their link and how they contribute to operational effectiveness and efficiency across different industries. To ensure cost-effective fulfilment supply chain management relies heavily on logistical operations that encompass everything from sourcing raw materials to delivering the final product. This paper delves into the intricacies of this interconnection highlighting the significance of collaboration integrating technology sharing real-time data and strategic planning. Furthermore, we will demonstrate how aligning supply chain management and logistics harmoniously fosters agility, resilience, and responsiveness. By utilizing case studies and factual evidence, we will illustrate how these interconnected disciplines enable adaptability to market changes while enhancing customer satisfaction and gaining an edge. Ultimately, this report asserts that the interdependence between logistics and supply chain management serves as an enabler for company success in a complex global landscape with high demands. The insights presented in this article aim to benefit practitioners, policymakers, and researchers by providing an understanding of this relationship while paving the way, for innovation, growth, and sustainability in today’s world.